К вопросу об истинной исторической роли Евфросинии Полоцкой - Рассадін, Сергій Євгенович; Rassadin, Sergey (Східноєвропейський національний університет імені Лесі Українки, 2015)
В статье анализируются некоторые источники об Евфросинии Полоцкой, а также соответствующая историография. Делается вывод о практическом неучастии Евфросинии Полоцкой в политике. На этом фоне особенно ярка еѐ роль как духовной просветительницы, организатора монастырской церковной жизни. In this article some of the sources about this saint, as well as relevant historiography are analyzed. It is concluded that Euphrosyne practically did not participate in politics. On this background, her role as a spiritual enlightener, organizer of the monastic life of the Church is especially bright.
To the Question of the True Historical role of Euphrosyne of Polatsk
Keywords: духовность; политизация; святая; spirituality; politicization; saint